6sin²x+cosx-5=0
6(1-cos²x)+cosx-5=0
-6cos²x+cosx+1=0
cosx=y;-6y²+y+1=0
6y²-y-1=0
y₁=1/2;y₂=-1/3
1) cosx=1/2
x=±π/3+2πn,n∈Z
2) cosx=-1/3
x=±arccos(-1/3)+2πk,k∈Z
1a) 2π≤π/3+2πn≤3π
5π/3≤2πn≤8π/3
5/3≤2n≤8/3
5/6≤n≤8/6
n=1⇒x=π/3+2π•1=7π/3
1б) 2π≤-π/3+2πn≤3π
7π/3≤2πn≤10π/3
7/3≤2n≤10/3
7/6≤n≤10/6
целых n нет
Аналогично для 2) случая
Пошаговое объяснение:
6sin²x+cosx-5=0
6(1-cos²x)+cosx-5=0
-6cos²x+cosx+1=0
cosx=y;-6y²+y+1=0
6y²-y-1=0
y₁=1/2;y₂=-1/3
1) cosx=1/2
x=±π/3+2πn,n∈Z
2) cosx=-1/3
x=±arccos(-1/3)+2πk,k∈Z
1a) 2π≤π/3+2πn≤3π
5π/3≤2πn≤8π/3
5/3≤2n≤8/3
5/6≤n≤8/6
n=1⇒x=π/3+2π•1=7π/3
1б) 2π≤-π/3+2πn≤3π
7π/3≤2πn≤10π/3
7/3≤2n≤10/3
7/6≤n≤10/6
целых n нет
Аналогично для 2) случая
Пошаговое объяснение: